PROSEDUR PENGECEKAN DAN PENANGANAN HOTSPOT PADA PMS GARDU INDUK 150 KV PEMATANGSIANTAR MENGGUNAKAN METODE THERMOVISION - Ageng Kusmayadi; M Haikal Budi Utomo; Farid Sitorus (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The operational reliability of a Substation (GI) is a crucial factor in maintaining the continuity of electric power transmission. One of the components that significantly contributes to this reliability is the Disconnecting Switch (PMS), which is prone to localized temperature increases or hotspots caused by rising contact resistance, loose connections, corrosion, or high current loading. Unaddressed hotspots may lead to component failure, protection malfunctions, or sudden power outages. In this study, an inspection and condition analysis of the PMS at the 150 kV Pematangsiantar Substation was conducted using the thermovision method employing a FLIR E60 infrared camera. Temperature measurements were taken at various critical points such as clamps, conductors, insulators, and PMS terminals, and then compared with the reference standard SKDIR 0520 of PT PLN (Persero). The measurement results indicate that most points fall within the normal category (Δt ≤ 5°C), although several significant anomalies were identified—particularly on the PMS Bus II In Clamp, where the temperature difference Δt reached 31°C and inter-phase temperature deviations reached 25°C, categorized as Condition III, requiring immediate corrective action. These findings highlight the importance of condition-based maintenance using thermovision to enable early detection of thermal anomalies, prevent equipment damage, and enhance transmission system reliability.